Women’s Language Features On Bridgerton Cast Youtube Interview By Netflix - Ni Made Ayu Sri Undari Dewi (Denpasar Institute, 2023)
In sociolinguistics, study about language and gender exists which relates to the relationship between the language of male and female. The most popular study about the related topic is the study of women’s language features by Robin Lakoff. The way women and men in delivering content in a conversation have different characteristics and it is interesting to be studied hence we acknowledge how language is used by different genders, especially for women as the most frequent role to be appeared in the data source. This study aimed at identifying the types of women’s language and describing the functions of each feature applied by the female casts of Bridgerton in an interview video. The data in this study were taken from a YouTube video held by Netflix entitled “TUDUM: Extended Talent Panel”. The method used in collecting the data was the observation method along with the note-taking technique. The theory used to analyze the data was the theory of women’s language proposed by Lakoff (1995). The result of this study shows that there are seven women’s language features found in the Youtube interview video of Bridgerton cast such as lexical hedges or fillers, tag questions, rising intonation on declarative, empty adjectives, intensifiers, hypercorrect grammar, and avoidance of strong words. However, some women’s language features are absent in the video such as precise color terms, super-polite form, and emphatic stress. The most dominant feature used is the lexical hedges with a total of 3 types used by the female cast. This feature is used to indicate that the speaker is uncertain about their statements, to give preparation time before the statement, and to decrease the strength of the statement.Bridgerton